Pareto criterion and long-term perspective criterion under myopic discounting - Kang, Minwook (2019)
Under myopic discounting, which encompasses the famous psychological and economics model, hyperbolic discounting preferences, this paper shows that efficiency by the Pareto criterion is a sufficient condition for efficiency by the long-term perspective criterion. This result provides additional justification for Pareto-improving policies under myopic discounting by showing that such policies improve normative preferences as well. As an application of our result, we provide an example of Laibson's Pareto-improving consumption tax.